2016
DOI: 10.1080/10410236.2015.1099501
|View full text |Cite
|
Sign up to set email alerts
|

Communication, Reasoning, and Planned Behaviors: Unveiling the Effect of Interactive Communication in an Anti-Smoking Social Media Campaign

Abstract: This study examines direct and indirect effects of interactive communication in an antismoking social media campaign. To that end, we pose a multitheoretical framework that integrates communication mediation models and the Theory of Planned Behavior. To test the theorized model, we conducted an experiment using a two-group pretest-posttest design. Participants (N = 201) were randomly assigned into two experimental conditions: "campaign message reception only" as a control group and "message reception and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 45 publications
1
62
0
Order By: Relevance
“…We found one study evaluating an anti-smoking Facebook campaign for college students 24 , though we excluded this study because our primary focus in this review was smoking cessation rather than prevention. In total, 7 studies met our inclusion criteria, all of which were published since 2014.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found one study evaluating an anti-smoking Facebook campaign for college students 24 , though we excluded this study because our primary focus in this review was smoking cessation rather than prevention. In total, 7 studies met our inclusion criteria, all of which were published since 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Study samples ranged from 26% to 77% male. Four studies were randomized controlled trials 24,27,28,30 , one study employed a quasi-experimental design 25 , and the remaining three studies were pilot or initial feasibility studies. 26,29,31 We also identified three articles reporting secondary outcomes 3234 and one study protocol 35 corresponding to the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Social support is important for behavior change broadly, 1315 and ample evidence indicates that existing social media groups can provide informational and emotional support to cancer survivors and caregivers. 16–18 Online communities have been linked to increased empowerment 19 and retention 20 ; engagement with the communities has been linked to behavior change success for weight loss, smoking cessation, and other cancer-related behaviors, 8,21,22 although some effects are small. 2325 Additionally, structured short message service and text messages to generate forum discussions, provide reminders, or offer tips and strategies have been effective build-ins.…”
Section: Key Principles Of Social Media To Enhance Cancer Prevention mentioning
confidence: 99%
“…For example, a study found that participation in cocreating antismoking campaign content on Facebook produced greater information searching and intention to quit than simply viewing the content online. 22 …”
Section: Key Principles Of Social Media To Enhance Cancer Prevention mentioning
confidence: 99%
“…Social support is important for behavior change broadly, [13][14][15] and ample evidence indicates that existing social media groups can provide informational and emotional support to cancer survivors and caregivers. [16][17][18] Online communities have been linked to increased empowerment 19 and retention 20 ; engagement with the communities has been linked to behavior change success for weight loss, smoking cessation, and other cancer-related behaviors, 8,21,22 although some effects are small. [23][24][25] Additionally, structured short message service and text messages to generate forum discussions, provide reminders, or offer tips and strategies have been effective build-ins.…”
Section: Social Support Influence and Normsmentioning
confidence: 99%